PENGEMBANGAN MEDIA ZATOPIA BERBASIS ANDROID BERBANTUAN SMART APPS CREATOR (SAC) DALAM UPAYA PENINGKATAN HASIL BELAJAR IPAS (MATERI WUJUD ZAT DAN PERUBAHANNYA) KELAS IV DI SD NEGERI KALIBANTENG KIDUL 01 KOTA SEMARANG - Oktavia, Dwiana; Widagdo, Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study develops application learning media and assesses the feasibility of Android-based zatopia learning media assisted by Smart Apps Creator (SAC) on substances and their changes in elementary school IPAS learning. The ADDIE development model with the Research & Development (R&D) research type was used in the study. 22 fourth grade students of SDN Kalibanteng 01 Semarang City as subjects in the study. Purposive sampling technique as a sampling where 6 students were selected based on low, medium and high learning outcomes. The research was conducted from November 2024 to January 2025. Data collection used interview, observation, questionnaire, documentation, and test techniques. Data were analyzed using normality test, paired sample t test, and n-gain test. Ethiopian substance media is categorized as very feasible to use with a percentage of feasibility of 95.83% media experts, 89.47% material experts, 90% language experts, 96% teacher responses and 95% student responses. The results of the media feasibility analysis with the paired sample t-test obtained a significance value of 0.00, meaning that there is a difference in the average pretest and posttest. The average pretest score is 67.75 and posttest 88.44 from these results obtained an n-gain value of 0.64 which is quite effective. It is concluded that zatopia learning media is effective in improving student learning outcomes, because there are differences in scores before learning using zatopia media and after learning using zatopia media, student scores increase.